Rhetorical Strategies in Zakir Naik’s Speech: A Critical Discourse Analysis Approach - Ahmad Rizal Abdullah; Fitriansal Fitriansal; Ashar Pramono (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2025)
This study explores the rhetorical strategies employed by Dr. Zakir Naik in one of his public speeches, focusing on how persuasion is constructed through Aristotle’s rhetorical appeals: ethos, pathos, and logos. Using a descriptive qualitative method, the research analyzes a selected speech transcript to uncover how language and argumentation are strategically used to influence audiences in a religious and intercultural context. Drawing on Aristotle's classical rhetorical theory as the main analytical framework, the study identifies how Dr. Naik establishes credibility (ethos), appeals to emotion (pathos), and constructs logical reasoning (logos) to strengthen his message. The analysis reveals that Dr. Naik effectively blends these rhetorical elements to assert religious authority, counter opposing viewpoints, and engage audiences from diverse backgrounds. This study contributes to the understanding of rhetorical discourse in contemporary religious communication and provides insight into how language can be used as a powerful tool for persuasion in cross-cultural settings.